Antimicrobial Resistance and Biofilm Formation in Coagulase Negative Staphylococci Isolated from Bovine Clinical Mastitis - Poshiya, Prakruti J; Javia, Bhavesh B; Ghodasara, Sanjay N; Bhadaniya, Amit R; Khambam, Shobha (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Bovine mastitis is a common and economically significant disease that affects dairy cows and buffaloes. Staphylococci are considered  as a most common cause of bovine mastitis. The present research work was undertaken with the objective to isolate and identify  coagulase-negative staphylococci (CoNS) by cultural, biochemical, and molecular methods from bovine mastitic milk samples, and to  study their antimicrobial resistance patterns as well as the biofilm-producing ability. The investigation was carried out on 281 bovine  clinical mastitis milk samples collected in and around Junagadh. Based on cultural and molecular methods, 34.87% (98/281) samples  yielded Staphylococcus isolates. Through the conventional standard tube coagulation test, 16.72% (47/281) isolates were identified as  CoNS. Mannitol fermentative patterns revealed 36.17% (17/47) CoNS isolates as fermentative, while 63.82% (30/47) CoNS isolates as  non-fermentative. CoNS isolates showed high resistance against penicillin-G (64.95%), followed by erythromycin (57.34%), while the  least resistance was observed against oxytetracycline (17.02%). Out of 47 CoNS isolates, 76.59% (36/47) were biofilm producers, while  23.40% (11/47) were non-biofilm producers.
Keywords: Biofilm,; Bovine; Clinical mastitis,; CoNS.